IMPLEMENTASI METODE RAPID APPLICATION DEVELOPMENT DALAM PERANCANGAN SISTEM INFORMASI INVENTARIS BARANG UPTB UPPD SAMSAT LOMBOK TENGAH - M. Saiful Akram; Mohammad Taufan Asri Zaen (Journal of Research and Publication Innovation, 2024)
UPTB UPPD SAMSAT Central Lombok they still use the data collection process using a simple method, namely using Excel to record goods data collection. This research aims to create an inventory system application which aims to reduce the risk of errors occurring compared to a manual recording system. The method used is the RAD method. This method is an information system development method that is considered to emphasize short development cycles, so it is considered appropriate to use in developing this inventory system. RAD uses an iterative method in developing a system of stages that support this method, namely define the requirements, prototype, receive feedback and finalize software. The results of this research are an inventory application interface that is used to collect goods data more quickly and accurately.